Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Muatan IPA Kelas V - Ila Israwaty; Usman; Nurul Azmi Multazam. H (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research was motivated by the low learning achievements of students class V science content at UPT SD Negeri 1 Arawa, Sidenreng Rappang Regency. The type of research used is classroom action research (PTK) which aims to determine improvement student learning processes and achievements in science content class V by applying Problem Based Learning model. The data collection techniques used are observation, tests and documentation. The subjects of this research were 30 class V teachers and students, consisting of 16 male students and 14 female students. The research was carried out in two cycles, each cycle consisting of 2 meetings. In cycle I, the research results from the teacher aspect in good qualifications, namely 80%, from the student aspect they were sufficient qualifications, namely 70% and the learning result tests in sufficient qualifications. Meanwhile, cycle II the research results from the teacher aspect in good qualifications, namely 93%, from the student aspect they were in good qualifications, namely 85% and the learning result tests in good qualifications. The conclusion this research that application of the Problem Based Learning model can improve student learning processes and achievements in class V science content at UPT SD Negeri 1 Arawa, Sidenreng Rappang Regency.